2014
DOI: 10.1007/s11250-014-0630-5
|View full text |Cite
|
Sign up to set email alerts
|

Farmers’ perceptions of goat kid mortality under communal farming in Eastern Cape, South Africa

Abstract: Rearing of goats under communal farming conditions is characterised by high kid mortality and low weaning percentages. A survey was conducted to determine farmers' perceptions on the causes of kid mortality during summer under the communal farming system in Nkonkobe Local Municipality in the Eastern Cape, South Africa. This was done by administering questionnaires to a total of 162 respondents in 14 villages around Nkonkobe Local Municipality. The study showed that majority of farmers (75 %) keep flock sizes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 11 publications
2
27
0
Order By: Relevance
“…In Sub-Saharan Africa, communal grazing systems were observed, where goat herds of small farmers living in the villages were raised together (GWASE et al, 2009), which differs from the system observed in Paraíba, where small farmers own the lands where they raise their animals. Studies in South Africa and Kenya show the occurrence of diseases in small ruminants as a limiting factor to production (KOSGEY et al, 2008;SLAYI et al, 2014), which was also observed in the present study. However, in South Africa, incentive programs were implemented towards the commercialization and genetic improvement of herds that favored the productivity of native breeds (ROETS; KIRSTEN, 2005;MOHLATLOLE et al, 2015), a fact which was not observed in this research, where the goat breeds that had some genetic improvement, mainly dairy breeds, originated from exotic breeds such as Saanen and Anglo-Nubian.…”
Section: Resultssupporting
confidence: 88%
“…In Sub-Saharan Africa, communal grazing systems were observed, where goat herds of small farmers living in the villages were raised together (GWASE et al, 2009), which differs from the system observed in Paraíba, where small farmers own the lands where they raise their animals. Studies in South Africa and Kenya show the occurrence of diseases in small ruminants as a limiting factor to production (KOSGEY et al, 2008;SLAYI et al, 2014), which was also observed in the present study. However, in South Africa, incentive programs were implemented towards the commercialization and genetic improvement of herds that favored the productivity of native breeds (ROETS; KIRSTEN, 2005;MOHLATLOLE et al, 2015), a fact which was not observed in this research, where the goat breeds that had some genetic improvement, mainly dairy breeds, originated from exotic breeds such as Saanen and Anglo-Nubian.…”
Section: Resultssupporting
confidence: 88%
“…Nevertheless, one needs to keep in mind that goat production efficiency cannot be measured in saleable livestock numbers only, since raising goats is considered an insurance against emergencies by these farmers. Farmers' perception of goat kit mortality under communal farming conditions in South Africa has been surveyed, whereby ectoparasites (predominantly ticks) scored high and were perceived a major cause of mortality [10].…”
Section: Introductionmentioning
confidence: 99%
“…In South Africa, major causes of kid mortality were tick-borne gall sickness diseases, endoparasites and ecto-parasites [12]. In another study, pre-weaning mortality rate of Angora kids was 11.5 per cent, caused by predators (39%), weak kids which needed help with suckling (19 %), does having no milk (7%) and does abandoning their kids (7%).…”
Section: Goat Kid Mortality: Major Challengementioning
confidence: 98%